Unbundling the complexity of performance management of healthcare providers in the Middle East - Daicy Vaz; Wardah Qureshi; Yama Temouri; Vijay Pereira (IIM Ranchi Journal of Management Studies)
Purpose – Previous research provides adequate evidence on performance management (PM) for hospitals and healthcare providers; however, less is known about their individual and PM appraisal process. Additionally, there is limited research exploring PM in the Middle Eastern context. This study investigates PM practices in the Middle Eastern healthcare industry. Design/methodology/approach – This study adopts the qualitative research methodology through semi-structured interviews of healthcare professionals in Kingdom of Saudi Arabia and the United Arab Emirates. Thematic analysis was adopted for analyzing this qualitative data. Findings – The main findings have uncovered different facets of appraisal challenges for both the appraiser (i.e. manager) and the appraisee (i.e. employee). These challenges include communication deficits, lack of goal setting standards and regular meeting updates in order to ensure employee satisfaction and motivation in the workplace. Research limitations/implications – This study has significant implications for policymakers in Middle Eastern hospitals in terms of implementing PM for their staff. Moreover, future studies can conduct in-depth analysis and provide comparison between public and private sectors in the Gulf countries. Originality/value – This study is one of the first to portray challenges involved in conducting PM in the Middle East healthcare sector specifically in the UAE and Kingdom of Saudi Arabia (KSA), both from the perspectives of the appraiser and appraisee.